Postvaccination SARS‐CoV‐2 infections among skilled nursing facility residents and staff members — Chicago, Illinois, December 2020–March 2021. Issue 6 (4th June 2021) - Teran, Richard A.; Walblay, Kelly A.; Shane, Elizabeth L.; Xydis, Shannon; Gretsch, Stephanie; Gagner, Alexandra; Samala, Usha; Choi, Hyeree; Zelinski, Christy; Black, Stephanie R.
Abstract : This article describes 22 cases of breakthrough SARS‐CoV‐2 infection among over 14, 000 fully vaccinated skilled nursing facility residents and staff. The majority of such infections were asymptomatic or were associated with mild symptoms, and there was no intra‐ facility spread related to these cases. This report suggests that postvaccination breakthrough infections are rare, but also confirms that vaccines do not offer 100% protection even in nonimmunosuppressed hosts, thus underscoring the need for studies of vaccine efficacy in immunosuppressed transplant recipients.